2008
DOI: 10.1097/01.aids.0000343766.00573.15
|View full text |Cite
|
Sign up to set email alerts
|

Risk behaviour, sexually transmitted infections and HIV among long-distance truck drivers: a cross-sectional survey along national highways in India

Abstract: Low self-risk perception for HIV (9.9%), low consistent condom use with non-paid partners (18.6%) and wives (3%), low reported exposure to any interventions (25.6%) and low levels of ever having taken an HIV test (16.5%) make truckers an important bridge population requiring strengthened interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
88
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(94 citation statements)
references
References 13 publications
(14 reference statements)
5
88
0
1
Order By: Relevance
“…[21,22,29,30] In this study, the sex trade along the highway was characterized by age-disparate rivalry and territorial boundaries. Territorial segregation was established to limit the intensity of competition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21,22,29,30] In this study, the sex trade along the highway was characterized by age-disparate rivalry and territorial boundaries. Territorial segregation was established to limit the intensity of competition.…”
Section: Discussionmentioning
confidence: 99%
“…[36,40] The necessity to practice safe sex is in time substituted by feelings of trust, which conjures the need for closeness, resulting in unprotected sex. [30,41] In this study some FSWs mentioned that they come across clients who refused to utilize free Choice condoms provided by the South African government at public health facilities, insisting on commercialized brands costly for FSWs to buy. [39] A study by Baker et al [42] explored custom-fitted male condoms as a sexual health intervention in Cape Town, and outlined concerns expressed by heterosexual males with regard to use of free government ( Choice ) condoms, possibly relevant to truck drivers in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Truck drivers play an important role in HIV/AIDS transmission in many countries (Pandey et al, 2008, Sunmola, 2005. Previous report in Bangladesh and India found HIV prevalence of 15.9% and 17.8% respectively among long distance drivers (Gibney et al, 2003, Manjunath et al, 2002.…”
Section: Hiv Infection Among Long Distance Truck Driversmentioning
confidence: 99%
“…Studies in other countries have shown that life conditions of truck drivers makes them come into contact with dangerous behavior such as having unhealthy sexual partners and drug abuse (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%